The Impact Of Transfer Pricing, Thin Capitalization, And Capital Intensity On Tax Evasion, With Sales Growth Serving As A Moderating Component. Food & Beverage Sector Companies Listed On The Indonesia Stock Exchange: Empirical Study (2019-2023) - Chandra Surya Zebua; Regina Jansen Arsjah (UNIVED Press, 2025)
This study aims to analyze the effect of transfer pricing, thin capitalization, and capital intensity on tax avoidance, and to evaluate the role of sales growth as a moderating variable. The phenomenon of tax avoidance is a crucial issue in the context of economic globalization, especially in the increasingly complex and cross-jurisdictional corporate sector. This study uses a quantitative approach with secondary data obtained from the annual financial reports of food and beverage companies listed on the Indonesia Stock Exchange (IDX) during the 2019-2023 period. The analysis method used is panel data regression with the Fixed Effect Model (FEM) approach. The results of the study indicate that transfer pricing, thin capitalization, and capital intensity have a significant negative effect on the effective tax rate (ETR), which is an indicator of tax avoidance. In addition, the sales growth variable is proven to strengthen the influence of the three variables on tax avoidance, indicating that companies with high sales growth tend to be more aggressive in carrying out tax planning. These findings provide important implications for tax regulators to tighten supervision of transfer pricing practices and complex corporate capital structures, especially in companies experiencing rapid growth.